Southeast Kansas Weather Summary - 2020 - G. F. Sassenrath; M. Knapp; X. Lin (Kansas Agricultural Experiment Station Research Reports, 2021)
This is a summary of the weather conditions in southeast Kansas during the 2019/2020 growing season. The wet weather pattern that began in 2019 continued into the spring of 2020, creating adverse conditions for spring crop establishment. Dry conditions during the summer and fall limited crop and pasture production. Temperatures were very near the 10-year averages at each location.
Keywords: weather; rainfall; temperature; growing degree days; cumulative rainfall; southeast Kansas